2018
DOI: 10.1021/acsami.8b11677
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Photocurable Three-Dimensional Printed Nerve Guidance Channels with Aligned Cryomatrix Lumen for Peripheral Nerve Regeneration

Abstract: Repair and regeneration of the critically injured peripheral nerves is one of the most challenging reconstructive surgeries. Currently available and FDA approved nerve guidance channels (NGCs) are suitable for small gap injuries, and their biological performance is inferior to that of autografts. Development of biomimetic NGCs with clinically relevant geometrical and biological characteristics such as topographical, biochemical and haptotactic cues could offer better regeneration of the long gap complex nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 54 publications
(116 reference statements)
1
62
0
Order By: Relevance
“…The photocurable capability of PGS-M enhances the existing strengths of PGS by allowing the material to be cross-linked at lower temperatures and pressures. [15,16] Further validation is required to confirm this relationship but PGS-M is generating much interest as a biomaterial. [15] The ease with which PGS-M can be synthesized together with the adaptability of its physical properties and suitability for use with different cell types, makes PGS-M an attractive candidate for an extensively deployed biomaterial.…”
Section: Doi: 101002/marc201900484mentioning
confidence: 99%
“…The photocurable capability of PGS-M enhances the existing strengths of PGS by allowing the material to be cross-linked at lower temperatures and pressures. [15,16] Further validation is required to confirm this relationship but PGS-M is generating much interest as a biomaterial. [15] The ease with which PGS-M can be synthesized together with the adaptability of its physical properties and suitability for use with different cell types, makes PGS-M an attractive candidate for an extensively deployed biomaterial.…”
Section: Doi: 101002/marc201900484mentioning
confidence: 99%
“…However, compared with natural biological materials, their biocompatibility is poor. Several synthetic materials, such as PCL (Singh et al, 2018), poly(lactic acid-co-glycolic acid) (PLGA) (Radulescu et al, 2007), poly(ethylene glycol) (PEG) (Christopher et al, 2015;Evangelista et al, 2015), poly(glycerol sebacate) (PGS) (Dharaminder et al, 2018), polypyrrole (PPy) (Weng et al, 2012) and carbon nanotubes (CNTs) (Lee et al, 2018a) have been used alone or in combination with natural polymers for 3D-printed NGCs.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Traditional NGCs are FDA‐approved conduit guides for the regeneration of injured nerve over small gaps, but these have been found to be clinically inferior compared to nerve autografts, as well nonsuitable for the regeneration of long‐gap complex nerve injuries. However, Singh et al () described the augmented regenerative potentiation of 3D‐printed cryogel‐filled NGCs for enhanced and successful regeneration of critically‐injured rat sciatic nerves. Their results indicated that guided‐regeneration, via 3D‐printed cryogel‐filled NGCs, led to a comparable regain of rat sciatic nerve physiology and cellular function compared to the gold‐standard autografts (Singh et al, ).…”
Section: Applications Of Cryogelsmentioning
confidence: 99%
“…However, Singh et al () described the augmented regenerative potentiation of 3D‐printed cryogel‐filled NGCs for enhanced and successful regeneration of critically‐injured rat sciatic nerves. Their results indicated that guided‐regeneration, via 3D‐printed cryogel‐filled NGCs, led to a comparable regain of rat sciatic nerve physiology and cellular function compared to the gold‐standard autografts (Singh et al, ).…”
Section: Applications Of Cryogelsmentioning
confidence: 99%